IMPACT OF 1 % METHACRYLIC ACID METHYL ESTER ON LECTINOCHEMICAL CHARACTERISTICS OF THE GLANDULAR AREA OF THE RAT HARD PALATE IN HELIX POMATIA LECTIN PROBING - Yeroshenko G.А.; Tymoshenko, Yu.V.; Hasiuk, N.V.; Udaltsova, K.A.; Ulanovska-Tsyba, N.A.; Shevchenko, K.V.; Haletka Ye.І. (World of Medicine and Biology, 2024)
The findings of the study have established that the effect of 1 % methacrylic acid methyl ester led to enhanced expression of receptors of the corneal layer of the epithelium throughout the entire experimental period, indicating the irritating effect of the ester, whereas the receptors of the granular, spinous and basal layers of the epithelium increased to the normal values only by day 14, demonstrating a compensatory adaptation mechanism to the action of methacrylate on the structural components of the epithelium of the glandular area of the rat hard palate. The lamina propria showed changes in fibroblasts and collagen fibers, characterized by an increased degree of conjugation with receptors to Helix pomatia lectin.